Breaking the Gastroparesis Bottleneck: Gastric Peroral Endoscopic Myotomy versus Pyloroplasty—a Narrative Review - Sharma, Zubin; Sisodia, Shubham; Choudhary, Neha; Rinkesh, Bansal; Choudhuri, Gourdas (Journal of Digestive Endoscopy, 2025)
Gastroparesis is a chronic gastric motility disorder characterized by delayed gastric emptying and debilitating symptoms. In refractory cases, interventions targeting the pylorus (gastric peroral endoscopic myotomy [G-POEM] and surgical pyloroplasty) have emerged as effective therapeutic options. This narrative review compares the efficacy, safety, durability, and cost-effectiveness of G-POEM and pyloroplasty in adult patients with medically refractory gastroparesis.Both G-POEM and pyloroplasty demonstrate comparable clinical efficacy, with 70 to 80% of patients achieving symptom improvement and enhanced gastric emptying, irrespective of underlying etiology (idiopathic, diabetic, or post-surgical). G-POEM offers advantages in procedural time, recovery, complication rates, and cost, while surgical pyloroplasty shows marginally superior improvements in objective gastric emptying in select cohorts. Long-term durability is comparable, though symptom recurrence may affect up to 30 to 50% by 5 years. G-POEM is repeatable and preserves future surgical options, whereas surgical pyloroplasty remains a definitive intervention.Both G-POEM and pyloroplasty are effective, safe, and durable interventions for refractory gastroparesis. G-POEM offers a minimally invasive, cost-effective alternative with similar efficacy, making it a preferred first-line intervention in appropriately selected patients. Individualized therapy based on anatomy, expertise, and patient preference is key to optimizing outcomes.
Keywords: gastroparesis; G-POEM; pyloroplasty; myotomy; gastric motility; GCSI